2018
DOI: 10.1002/jbmr.3581
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Doses of Sclerostin Antibody Do Not Induce Osteonecrosis of the Jaw (ONJ) in Rats with Experimental Periodontitis

Abstract: Antiresorptive agents, such as bisphosphonates and denosumab, are frequently used for the management of osteoporosis. Indeed, both medications decrease the risk of osteoporotic fractures; however, these medications are associated with rare but potentially severe side effects, such as osteonecrosis of the jaw (ONJ). ONJ, defined as an area of exposed bone in the maxillofacial region that lasts for 8 weeks, often presents with significant pain and infection and can lead to serious complications. Interestingly, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 62 publications
(95 reference statements)
2
21
0
Order By: Relevance
“…The systemic Scl-Ab group showed significant enhancement of alveolar bone healing after surgery including bone volume, bone fill, and bone mineral density based on μCT analysis. These findings are also consistent with the previous reports about enhancing vertebral structural bone parameters using Scl-Ab in osteoporosis models 32 , and alveolar bone in a molar extraction model 22 . Moreover, histomorphometric analysis confirmed that the percentage area of new bone fill was significantly greater by systemic delivery of Scl-Ab versus control, as well as a tendency for increased cementogenesis and less root resorption.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The systemic Scl-Ab group showed significant enhancement of alveolar bone healing after surgery including bone volume, bone fill, and bone mineral density based on μCT analysis. These findings are also consistent with the previous reports about enhancing vertebral structural bone parameters using Scl-Ab in osteoporosis models 32 , and alveolar bone in a molar extraction model 22 . Moreover, histomorphometric analysis confirmed that the percentage area of new bone fill was significantly greater by systemic delivery of Scl-Ab versus control, as well as a tendency for increased cementogenesis and less root resorption.…”
Section: Discussionsupporting
confidence: 93%
“…Considering the unique characteristics of Scl-Ab for the promotion of bone density in a variety of contexts, several studies have reported the ability of Scl-Ab to address unmet dental needs. Scl-Ab administration has previously shown inhibition of periodontal disease progression 32 , enhancement of the recovery from periodontal disease 21 , and increased osteointegration and bone regeneration around dental implants 23 . Moreover, in two large clinical studies, a single case of osteonecrosis of the jaw (ONJ) bone was reported 17,18,31,32 whereas antiresorptive agents including bisphosphonates and denosumab are associated with an increased risk of ONJ.…”
Section: Discussionmentioning
confidence: 99%
“…SD rats (8 weeks of age) were randomly divided into two groups: one group of rats was sham-operated, and another group of rats underwent ovariectomy. OVX rats and sham rats were provided by Charles River Laboratories, and the OVX group underwent bilateral OVX using a sterile technique as described previously [48]. Rats in both groups were fed for 4 weeks after surgery.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…One of the risk factors for using anti-resorptive treatment using either bisphosphonates or anti-RANKL antibody denosumab is osteonecrosis of the jaw [ 38 ]. In a study comparing the clinically relevant doses of the sclerostin antibody with bisphosphonates in an experimental periodontitis rat model after ovariectomy, no osteonecrosis developed and also less alveolar bone was lost [ 39 ]. Furthermore, all bone anabolic parameters improved after sclerostin antibody treatment [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study comparing the clinically relevant doses of the sclerostin antibody with bisphosphonates in an experimental periodontitis rat model after ovariectomy, no osteonecrosis developed and also less alveolar bone was lost [ 39 ]. Furthermore, all bone anabolic parameters improved after sclerostin antibody treatment [ 39 ]. Progressive periodontitis eventually leads to tooth loss, hereby solving the chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%